OWeB: A Framework for Offline Web Browsing - Ananthanarayanan, Ganesh; Blagsvedt, Sean; Toyama, Kentaro (Latin American Web Congress (LA-WEB), 2006)
Internet browsing is highly dependent on the real-time network availability and speed. This becomes a significant constraint when browsing over slow and intermittent networks. In this paper, we describe a readily deployable system designed for web browsing over slow, intermittent networks – OWeB, that is minimally dependent on the real-time network availability and requires no changes on the part of the web servers. The system subscribes to Really Simple Syndication (RSS) feeds from web servers and pre-fetches all new content as specified in the feed. Since the RSS feeds are published by web servers they give accurate information about the new and updated content. Efficiency of network usage is achieved by employing standard techniques to handle intermittent networks, and near-complete utilization of all downloaded content results in better resilience in case of interrupted data downloads. We observed a co-relation between the items in an RSS feed and the homepage of the corresponding website (i.e.) the feed items essentially define the content section of the homepage. As part of OWeB, we developed an algorithm for automatically extracting the template of home pages and then locally stitching the feed items into the template. This results in websites being up-to-date and fully available offline and bandwidth savings, as we only need to download the RSS feed to construct the homepage.